2015
DOI: 10.12738/estp.2016.1.0072
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Inclusive STEM Schools in the College and Career Readiness of Students in the United States: A Multi-Group Analysis on the Outcome of Student Achievement

Abstract: The most prominent option for finding a solution to the shortage of workers with STEM knowledge has been identified as specialized STEM schools by policymakers in the United States. The current perception of specialized STEM schools can be described as a unique environment that includes advanced curriculum, expert teachers, and opportunities for internships and immersion. This study highlights the college readiness of STEM school graduates in comparison with traditional high school graduates. Using 11th grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…A doctoral dissertation by Oner (2015) concluded that while some results of the comparisons run on a state data set were equivocal, T-STEM academies partially fulfilled their promise for some groups of students, over time, especially for Hispanic and economically disadvantaged students-students who were the target of the TSTEM efforts. Similarly, Erdogan and Stuessy (2015) found that student demographic variables (gender, ethnicity, socioeconomic status, and special education status) may influence the success of students attending STEM schools, but effect sizes were small, although favoring T-STEM schools. Overall, the results for studies of ISHSs in Texas pointed in a positive direction.…”
Section: Introductionmentioning
confidence: 91%
“…A doctoral dissertation by Oner (2015) concluded that while some results of the comparisons run on a state data set were equivocal, T-STEM academies partially fulfilled their promise for some groups of students, over time, especially for Hispanic and economically disadvantaged students-students who were the target of the TSTEM efforts. Similarly, Erdogan and Stuessy (2015) found that student demographic variables (gender, ethnicity, socioeconomic status, and special education status) may influence the success of students attending STEM schools, but effect sizes were small, although favoring T-STEM schools. Overall, the results for studies of ISHSs in Texas pointed in a positive direction.…”
Section: Introductionmentioning
confidence: 91%
“…Students had a statistically significant ( p < 0.05) improvement in their mathematics scores the year after their schools adopted and implemented STEM curriculum and instruction. Researchers noted in additional longitudinal studies that students who attended T‐STEM academies and those who attended traditional public high schools statistically significantly ( p < 0.05) increased their science and mathematics scores, but there was no statistically significant difference between T‐STEM schools and traditional public high schools in terms of students’ science and mathematics achievement (Erdogan & Stuessy, ; Sahin et al, ). Furthermore, there was no statistically significant ( p > 0.05) difference between students who enrolled in T‐STEM academies and students who enrolled in traditional public high schools in terms of their average mathematics achievement trajectory (Bicer et al, ; Young et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yapılan çalışmalar FeTeMM eğitiminin ve projeye dayalı öğretimin akademik başarıya olumlu etkisi olduğu belirtilmiştir (Erdogan, & Stuessy, 2015). Bu çalışmada FeTeMM eğitiminin özellikle fizik derslerinde yaygın olarak kullanılmasının teşvik edilmesi önerilmektedir.…”
Section: Sonuç Ve Tartışmaunclassified